(untitled) (UUM Journal of Legal Studies, 2020)
This paper focuses on the Rule of Law and it’s reach in terms of the stateless Indian in Malaysia. The term rule of law has been a term used by politicians to secure political mileage during election campaign periods and continues to be used upon formation of a new government. Regardless of its transcendent nature and noble assurance of a government of laws and not men, there would be gaps in the usage of the term rule of law as it does not reach all levels of community. As beneficent as the concept maybe, it does not serve to assist the stateless Indian community in securing employment in the state. Hence the significance of the research is to identify the gaps in the application of Rule of Law in Malaysia towards the stateless Indian. This study is a purely conceptual one which evaluates the constitutional concept of rule of law and its limitations in providing employment rights for Stateless Indians. The predominant research question is whether the Rule of Law as understood by constitutional philosophers helps mitigate the plight of the stateless Indian. It investigates that notion that perhaps stateless Indians are not stateless after all but have been given that categorisation so as to allow for their plight to be catapulted into the international sphere where customary international law and treaty law could in ideal circumstances apply to the stateless Indian. It proposes a thesis that regardless of how closely a State like Malaysia follows and upholds the rule of law, the stateless Indian Community in Malaysia will not necessarily enjoy second generation rights that ought to be made available to all human beings. The second generation right specifically referred to in this research is the right to employment for the stateless Indian.